FIFA and UEFA, a critical review of the two organizations through the lens of institutional theory and MacIntyre`s philosophical schema - Pouliopoulos, T.; Georgiadis, K. (Soccer & Society, 2021)
FIFA and UEFA are the two major football institutions in the global and European level, respectively. The recent scandals in both organizations and especially in FIFA, raised again discussion about the nature of governance in football institutions. This study focuses for the first time on the assessment of both organizations by using the tenets of institutional theory and MacIntyre`s virtues-goods-practice-institution schema. Through a review of the history of FIFA and UEFA, we identified the role of the context, agents and ethics. Our analysis shows that while FIFA has developed very much in terms of power and influence, both the agents and institutional context, have played a key role in the creation of a culture of corruption. On the other hand, UEFA had to comply with a stricter regulative system and powerful stakeholders, while its major agents appear to be less affected by corrupt practices, compared to those of FIFA.